1988
DOI: 10.1113/jphysiol.1988.sp017084
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive actions of descending dopaminergic tracts on cat and rat dorsal horn somatosensory neurones.

Abstract: SUMMARY1. The actions of dopamine (DA) and DA receptor specific agonists and antagonist ionophoretically applied in the spinal dorsal horn, and of focal electrical stimulation in the region of the supraspinal DA cell groups (A9 and All) were assessed on the somatosensory responses of dorsal horn neurones, in both the rat and cat. The neurones tested were multireceptive, giving reproducible responses to both noxious (using a mechanical pinch or radiant heat) and innocuous (using a motorized brush) cutaneous sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
82
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(93 citation statements)
references
References 29 publications
6
82
0
1
Order By: Relevance
“…The data are consistent with the A11 providing a descending D 2 receptor family-mediated tonic modulation of ophthalmic division trigeminal nociceptive afferents. The data are consistent with rat and cat spinal cord studies in which focal electrical stimulation in the region of the A11 dopamine cell group suppressed the nociceptive but not non-nociceptive responses of multireceptive neurons in the spinal cord dorsal horn (Fleetwood-Walker et al, 1988). The colocalization of CGRP in the A11 and the recently confirmed role for CGRP in migraine (Bigal et al, 2008;Ho et al, 2008), taken with other data on dopamine in migraine (Peroutka, 1997), suggest a possible role for the A11 in the disorder.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The data are consistent with the A11 providing a descending D 2 receptor family-mediated tonic modulation of ophthalmic division trigeminal nociceptive afferents. The data are consistent with rat and cat spinal cord studies in which focal electrical stimulation in the region of the A11 dopamine cell group suppressed the nociceptive but not non-nociceptive responses of multireceptive neurons in the spinal cord dorsal horn (Fleetwood-Walker et al, 1988). The colocalization of CGRP in the A11 and the recently confirmed role for CGRP in migraine (Bigal et al, 2008;Ho et al, 2008), taken with other data on dopamine in migraine (Peroutka, 1997), suggest a possible role for the A11 in the disorder.…”
Section: Discussionsupporting
confidence: 79%
“…As D 2 -like receptors (D 2 , D 3 , D 4 receptors) normally cause hyperpolarization and inhibit cell firing via an inhibition of cAMP formation (Missale et al, 1998), this suggests the A11 inhibitory effect is mediated by activation of D 2 -like receptors in the TCC. This interpretation is supported by data in the rat and cat spinal cord, in which the stimulus-evoked A11 effect was consistently and rapidly reversed by iontophoresis of a selective D 2 receptor antagonist (sulpiride) in the vicinity of the dorsal horn neurons tested (Fleetwood-Walker et al, 1988). Furthermore, iontophoretically applied dopamine or a D 2 receptor agonist (RU24213 [N-n-propyl-N-phenylethyl-4(3-hydroxyphenyl)ethylamine hydrochloride]) in the rat and cat spinal cord caused inhibition of nociceptive responses in these spinal cord neurons, reversed by a selective D 2 receptor antagonist.…”
Section: Discussionsupporting
confidence: 70%
“…There are extensive dopaminergic projections in the spinal cord (Skagerberg et al, 1982, Skagerberg and Bjorklund, 1985, Skagerberg et al, 1988, and a number of authors have demonstrated modulatory actions of dopamine in the cord (Carp and Anderson, 1982, Barasi and Duggal, 1985, Fleetwood-Walker et al, 1988, Hasegawa et al, 1990, Skoog and Noga, 1995, Kemnitz, 1997, Garraway and Hochman, 2001, Tamae et al, 2005. However, there is only a limited description on the distribution of the different dopamine receptors in spinal cord neurons (Dubois et al, 1986, Schambra et al, 1994, Yokoyama et al, 1994, van Dijken et al, 1996, Levant and McCarson, 2001, Zhao et al, 2007.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…At least a portion of these fibers are likely functional because stimulation of the parapyramidal area in the brain stem elicits 5-HT-dependent locomotor-like activity (Liu and Jordan 2005) and separate studies confirm the release of 5-HT and NA metabolites in the ventral horn of adult and neonatal rats during brain stem stimulation or exercise (Gerin et al 1994(Gerin et al , 1995Jordan and Schmidt 2002). Less data are available for the dopaminergic system; however, DA fibers and receptors are present in the rat spinal cord (Holstege et al 1996;Ridet et al 1992;Yoshida and Tanaka 1988) and are functional (Fleetwood-Walker et al 1988). The extent to which DA, 5-HT, or NA contributes to reflex and network modulation in the intact neonate is unknown.…”
Section: Functional Considerationsmentioning
confidence: 99%